HUKUM PERCERAIAN KARENA KEMURTADAN MENURUT KOMPILASI HUKUM ISLAM (Faculty of Law, University of Palembang, 2022)
When undergoing a household dipper, the problem will certainly be a challenge for married couples. Try to get through the economy, infidelity, disharmony, domestic violence, and the transfer of one of the beliefs of one married couple. In Islam, when one of the couples converts or apostates then the marriage becomes fasakh (broken) thus causing divorce. This is a concern for research to examine divorce law due to beliefs according to a compilation of Islamic law. The research method used in this study is descriptive qualitative research. This research is descriptive, which is research that describes an object and describes an event with a view to knowing the state of the object being studied. There is also the focus of the research is divorce law due to moving faith in one of the couples. Divorce is the abolition of a marriage at the demands of one of the married couples for reasons that are in accordance with the legislation accompanied by a pledge by the husband before a religious court hearing. In Islam, divorce is termed talaq. There are two types of divorce, namely divorce caused by husband's talaq and divorce over wife's lawsuit. Divorce law is divided into five, among others mandatory, sunnah, makruh, mubah, haram. While divorce caused by the transfer of beliefs of one of the married couples can result in divorce in article 116 letter (h) Compilation of Islamic Law asserts that divorce on the grounds of apostasy can only be granted if the apostasy causes insecurity in the household.